Changes in plasma amino acid profiles, growth performance and intestinal antioxidant capacity of piglets following increased consumption of methionine as its hydroxy analogue. Issue 6 (1st August 2014) - Li, Hao; Wan, Haifeng; Mercier, Yves; Zhang, Xiaoling; Wu, Caimei; Wu, Xiuqun; Tang, Li; Che, Lianqiang; Lin, Yan; Xu, Shengyu; Tian, Gang; Wu, De; et al.
Abstract : The aim of the present study was to determine whether early weaning-induced growth retardation could be attenuated by increased consumption of methionine asdl -methionine (DLM) ordl -2-hydroxy-4-methylthiobutyrate (HMTBA) in both lactating sows and weaned piglets. Therefore, diets containing DLM and HMTBA at 25 % of the total sulphur-containing amino acids (AA) present in the control (CON) diet were fed to lactating sows and weaned piglets and their responses were evaluated. Compared with the CON diet-fed sows, the HMTBA diet-fed sows exhibited a tendency ( P < 0·10) towards higher plasma taurine concentrations and the DLM diet-fed sows had higher ( P < 0·05) plasma taurine concentrations, but lower ( P < 0·05) isoleucine concentrations. Suckling piglets in the HMTBA treatment group had higher ( P < 0·05) intestinal reduced glutathione (GSH) content, lower ( P < 0·05) oxidised glutathione (GSSG):GSH ratio, and higher ( P < 0·05) plasma cysteine and glutathione peroxidase (GPx) activity than those in the CON and DLM treatment groups. The feed intake ( P < 0·05) and body weight of piglets averaged across post-weaning (PW) days were higher ( P < 0·05) in the HMTBA treatment group than in the DLM treatment group and were higher ( P < 0·05) and tended ( P < 0·10) to be higher, respectively, in the HMTBA treatment group than in the CON treatment group. Increased ( P < 0·05) GSSG content and GSSG:GSH ratio and down-regulated ( P < 0·05) expression of nutrient transport genes were observed in the jejunum of piglets on PW day 7 than on PW day 0. On PW day 14, the HMTBA diet-fed piglets had higher ( P < 0·05) intestinal GSH content than the CON diet-fed piglets and higher ( P < 0·05) plasma GPx activity, villus height and goblet cell numbers than the CON diet- and DLM diet-fed piglets. In conclusion, early weaning-induced growth retardation appears to be attenuated through changes in plasma AA profiles and elevation of growth performance and intestinal antioxidant capacity in piglets following increased consumption of methionine as HMTBA.